2015
DOI: 10.1002/ece3.1537
|View full text |Cite
|
Sign up to set email alerts
|

Grazing intensifies degradation of a Tibetan Plateau alpine meadow through plant–pest interaction

Abstract: Understanding the plant–pest interaction under warming with grazing conditions is critical to predict the response of alpine meadow to future climate change. We investigated the effects of experimental warming and grazing on the interaction between plants and the grassland caterpillar Gynaephora menyuanensis in an alpine meadow on the Tibetan Plateau in 2010 and 2011. Our results showed that grazing significantly increased nitrogen concentration in graminoids and sward openness with a lower sward height, sward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Furthermore, grazed plants have been shown to increase chlorophyll and photosynthetic enzymes concentration in remaining or new leaves, which consequently results in a higher total N concentration (Briske, ; Price, ). Indeed, plant nutrient enrichment is a common result of large herbivore grazing and has been reported in many ecosystems including forests (Riipi et al, ) and African savannas (McNaughton, ) and alpine meadows (Cao et al, ). However, it is noted that the effect of large vertebrates on grass N content may vary based on the intensity of grazing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, grazed plants have been shown to increase chlorophyll and photosynthetic enzymes concentration in remaining or new leaves, which consequently results in a higher total N concentration (Briske, ; Price, ). Indeed, plant nutrient enrichment is a common result of large herbivore grazing and has been reported in many ecosystems including forests (Riipi et al, ) and African savannas (McNaughton, ) and alpine meadows (Cao et al, ). However, it is noted that the effect of large vertebrates on grass N content may vary based on the intensity of grazing.…”
Section: Discussionmentioning
confidence: 99%
“…Competition for shared host plants between large grazing mammalian herbivores and smaller herbivores, such as arthropods, is a classic example of interaction among phylogenetically distinct groups. Recent meta‐analytical reviews of the literature find that, on average, the effects of large herbivores on smaller animal taxa are negative, both in terms of abundance and diversity (Foster, Barton, & Lindenmayer, ; Takagi & Miyashita, ; van Klink, van der Plas, van Noordwijk, WallisDeVries, & Olff, ); however, there is considerable variation in the outcome of individual studies including positive (Cao et al, ), negative (Pringle et al, ), and neutral effects (Riipi, Lempa, Haukioja, Ossipov, & Pihlaja, ) of large herbivores on insect populations. While some of this context‐dependency is attributed to differences in the spatial and temporal scale of the study, differences across systems in the processes linking large and small herbivores also play a significant role (Takagi & Miyashita, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, earlier-flowering plants (e.g., Kh and Cs; Fig. 2) are grazed by animals such as sheep, yaks, mice, and caterpillars (Zhao 2009, Cao et al 2015. A possible strategy of plants in a community for reducing herbivorous pressure is a short period of synchronous production of leaves, buds, and flowers, thereby satiating the herbivores (Aide 1991, Fenner 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Grime 1979). In Northern Tibet, Cao et al (2015) found that the levels of both plant species diversity and herbage biomass were higher in areas of a grazing ban, than in communal free grazing land with no grazing ban. In this study, interannual variations of standing herbage biomass were mainly determined by local precipitation and temperature (Table 1).…”
Section: Comparing the Benefits Of Grazing Exclusion Vs Grazing On Rmentioning
confidence: 99%